Prediction of the one-repetition maximum based on the maximum number of repetitions with submaximal loads in women. - Ursula Ferreira Julio; Valéria Leme Gonçalves Panissa; Emerson Franchini (Universidade Federal de Santa Catarina, 2011)
The objective of the present study was to determine equations that could be used to estimate the load corresponding to the one-repetition maximum (1RM) based on the maximum number of repetitions (MNR) using submaximal loads in bench press, lat machine pull-down and leg curl exercises in strength-trained women (n = 20; 22 ± 3 years; 61 ± 7 kg; 165 ± 4 cm). The first test was the 1RM test. Next, the subjects performed the MNR test at intensities of 70, 80 and 90% of 1RM for all exercises on different days. A multiple linear regression model was used for the determination of each equation. Two criteria were applied to accept the equation: adjusted R² value (adj.R² > 0.80) and percent error (PE < 10%). For all exercises, the equations met the two criteria: bench press: adjR² = 0.89; PE = 5%; lat machine pull-down: adjR² = 0.84; PE = 5%; leg curl: adjR² = 0.82; PE = 7%. The application of the equations developed will require the selection of a random load and the number of repetitions performed at the same load to identify 1RM. It is recommended that the number of repetitions be within the range observed in this study: bench press (1-21), lat machine pull-down (2-20), and leg curl (1-14).